2003
DOI: 10.1046/j.1365-2443.2003.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

ATPase/helicase motif mutants of Escherichia coli PriA protein essential for recombination‐dependent DNA replication

Abstract: Backgrounds : PriA protein, a DEXH-type helicase with C 2 C 2 zinc-finger motifs, plays essential roles in RecA-dependent modes of Escherichia coli chromosomal DNA replication, namely inducible and constitutive stable DNA replication (iSDR and cSDR respectively, which may be initiated from a D-loop or R-loop structure), and in repair of doublestranded DNA breaks generated by various genotoxic agents or spontaneously during the course of DNA replication. However, the roles of ATPase/ DNA helicase activities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 49 publications
(60 reference statements)
4
45
0
Order By: Relevance
“…The suggestion that cells lacking RecG and depleted of 39 ssDNA exonucleases suffer damage to their DNA as a result of unscheduled replication fork collisions is consistent with the fact that the problem largely disappears when the helicase activity of PriA is eliminated (Figure 8), especially as PriA helicase mutants reduce SDR (Tanaka et al 2003). Given that DrecG and DrnhA cells have in common a high level of cSDR initiated at R-loops (Kogoma 1997), it is also consistent with the fact that eliminating RNase HI mimics the effect of eliminating RecG (Figure 9).…”
Section: Discussionsupporting
confidence: 67%
“…The suggestion that cells lacking RecG and depleted of 39 ssDNA exonucleases suffer damage to their DNA as a result of unscheduled replication fork collisions is consistent with the fact that the problem largely disappears when the helicase activity of PriA is eliminated (Figure 8), especially as PriA helicase mutants reduce SDR (Tanaka et al 2003). Given that DrecG and DrnhA cells have in common a high level of cSDR initiated at R-loops (Kogoma 1997), it is also consistent with the fact that eliminating RNase HI mimics the effect of eliminating RecG (Figure 9).…”
Section: Discussionsupporting
confidence: 67%
“…Although helicase-deficient PriA proteins retain the ability to assemble a primosome and to complement the DNA repair and growth defects associated with a priA null allele (Zavitz and Marians 1992), they reduce SDR quite substantially (Tanaka et al 2003), a fact consistent with genetic data indicating that the K230R derivative may not be able to initiate replication at D loops . In doing so, we believe they reduce the chromosome pathology arising as a consequence of unscheduled DNA replication (Rudolph et al 2009a,b).…”
Section: Discussionsupporting
confidence: 53%
“…We previously reported that a D-loop like structure strongly stimulated ATPase activity of PriA (29). Similarly, A-fork [3Ј] DNA significantly activated PriA-mediated ATP hydrolysis (Fig.…”
Section: Nuclease Protection Analyses On Thementioning
confidence: 52%
“…Non-structured single-stranded DNA can also activate ATP hydrolysis by PriA in the absence of single-stranded DNAbinding protein (29). This activation is largely dependent on the presence of a 3Ј terminus (Fig.…”
Section: ј Terminus-dependent Bipartite Interaction Of Pria With Anmentioning
confidence: 99%